Pelayanan Perizinan pada Dinas Penanaman Modal dan Pelayanan Terpadu Satu Pintu ( DPMPTSP ) (Studi Peraturan Bupati Lombok Tengah Nomor 35 Tahun 2022 Tentang Penyelenggaraan Mal Pelayanan Publik) - Hidayat, Rahmad; Fitri, Sri Lela; Hidayatullah, Hidayatullah; Dermawan, M. Ariy (Jurnal Ilmiah Tata Sejuta STIA Mataram, 2024)
In Central Lombok Regional Regulation No. 35 of 2022 concerning the Implementation of Public Service Malls (MPP), which aims to provide fast, affordable and transparent services. The implementation of this MPP is under the auspices of the Department of Investment and One Stop Integrated Services (DPMPTSP) and in this research the focus is on licensing services at DPMPTSP through Public Service Mall innovation.This research aims to find out how licensing services are implemented at DPMPTSP through the Central Lombok Public Service Mall innovation and what factors influence it. The research approach used in this research is a qualitative descriptive research approach where the research results are obtained from interviews with service heads, service secretaries, MPP managers, DPMPTSP staff, service officers, and permit applicants. The results of this research found that the implementation of licensing services at the One Stop Investment and Integrated Services Service (DPMPTSP) through the Central Lombok Regency Public Service Mall innovation has gone as expected. This can be seen from the researcher's analysis using indicators of communication, resources, disposition and bureaucratic structure. Good communication between organizers and permit applicants is carried out through socialization both online and offline. Human resources are sufficient to carry out services, but after one year they experience obstacles due to a lack of human resources due to the increase in visitors. A clear disposition with standards that have been determined in accordance with statutory regulations. The bureaucratic structure that has been determined will simplify the licensing service process because it runs according to the SOP that has been determined. The combination of these four aspects means that the implementation of licensing services can be carried out properly. These four indicators are also included in what factors influence them. In implementing this policy there are also influencing aspects, namely: Initial information, licensing process, customer service, security, evaluation.